MANIPULACIÓN DE LA OVULACIÓN DEL FOLÍCULO DOMINANTE CON PROSTAGLANDINAEN DIFERENTES ESTADIOS DEL CICLO ESTRUAL SOBRE LAS TASAS REPRODUCTIVAS EN OVINOS CORRIEDALE - Urviola S., Martín (2005)
Sixty-five 3-4 years old Corriedale ewes were used from April to August 2002 to evaluate the effect of PGF2µ treatment at days 4 (GP4) and 10 (GP10) of the estrous cycle on (i) the percentage of estrus, (ii) variability within animals in the onset of estrus, (iii) the length of the treatment-estrus interval and, (iv) the rate of pregnancy. The estrous cycle was synchronized inserting intravaginal sponges impregnated with 30 mg of fluorogestone acetate (FGA) during 12 days. After the occurence of estrus (estrus = day 0), 20 ewes at day 4 (GP4) and 22 at day 10 (GP10) were treated with 0.175 mg of an analogue of PGF2µ. The 23 remaining ewes were not treated and kept as control group (GC). Estrus was detected by introducing vasectomized rams to the flock at 6, 12 and 17 h on daily basis. All FGA-synchronizated ewes showed estrus, as well as after the treatment with PGF2µ; however, the onset of estrus was significantly (p£ 0.01) earlier in GP4 (34:28 h) and GC (40:16 h) than in GP10 (47:45 h). GP4 presented smaller variability among ewes (sd=4:26) in the length of the treatment-estrus interval than GP10 (sd=7:06). Pregnancy rate (no return to estrus) at day 17 after breeding were similar in groups GP10 (77.3%) and GP4 (80.0%), but slightly higher in GC (91.3%). Pregnancy rate decreased by day 28 in all groups (63.6, 65.0 and 87.0%, respectively), and remaining like that until day 72, with the exception of GC (78.3%).